Finite element analysis and testing on the vibration mode of small grinding carriage in high-efficiency CNC grinding machine. (October 2020) - Zheng, Dateng; Zhang, Qing; Zhang, Jing; Yao, Haibiao; Yin, Sanfeng
Abstract: The small grinding carriage is a key component of the high-efficiency computerized numerical control (CNC) grinding machine. The machining of the small grinding wheel is the last process of the workpiece on the grinding machine, and its vibration performance has an important influence on the grinding precision. A novel low vibration grinding carriage using finite element analysis method (FEM) was designed to validate its vibration performance before producing. In this study, the finite element model of the small grinding carriage was established. The finite element calculation was performed using the Block Lanczos algorithm, and the first natural frequency of the small grinding carriage was 283.2 Hz. Besides, the experimental modal analysis method of ambient excitation was used to test and analyze the small grinding carriage assembled to a grinding machine. The modal parameters of the system structure were identified based on the theoretical auto power spectrum. The first five natural frequencies and damping ratios of the small grinding carriage were obtained. The accuracy of the recognition results was verified using the modal judgment criteria. The two methods cross-validated the structure design of the small grinding wheel, which can avoid resonance during machining. The results provided in this paper can serve as a reference for the subsequent structural optimization design.